2021
DOI: 10.52963/perr_biruni_v10.n2.04
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Learning-Teaching Conceptions and Technological Pedagogical Content Knowledge: A Structural Equation Modeling Study

Ufuk ULUÇINAR

Abstract: Competency in technological pedagogical content knowledge is one of the fundamental standards to become a qualified teacher in 21. century. Teachers are expected to have TPACK with technology integration efficacies in their classroom. This research aims to explain the roles of TPACK and its components on behaviorist and constructivist learningteaching conceptions. Designed as an explanatory research the current study employs hypotheses explaining causeresult connections amongst independent variables (knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The relationship between teachers' pedagogical knowledge and content knowledge with the implementation of cooperative learning shows a high positive correlation. Thus, the results obtained are in agreement with prior studies stating that mastery of content knowledge [24] and pedagogical knowledge [28] has a positive impact on the implementation of a studentcentered teaching approach. This finding is consistent with those by Melesse and Gulie [43], who stated that continuous professional development positively influenced the quality of teaching.…”
Section: Relationship Between Teachers' Content Knowledge Pedagogical...supporting
confidence: 91%
See 1 more Smart Citation
“…The relationship between teachers' pedagogical knowledge and content knowledge with the implementation of cooperative learning shows a high positive correlation. Thus, the results obtained are in agreement with prior studies stating that mastery of content knowledge [24] and pedagogical knowledge [28] has a positive impact on the implementation of a studentcentered teaching approach. This finding is consistent with those by Melesse and Gulie [43], who stated that continuous professional development positively influenced the quality of teaching.…”
Section: Relationship Between Teachers' Content Knowledge Pedagogical...supporting
confidence: 91%
“…Content knowledge refers to teachers' knowledge of subject matters that need to be mastered by teachers and learned by pupils. Teachers' content knowledge is important in order to implement the student-centered teaching approach [22]- [24]. In contrast, however, a study [25] found that teachers tend to implement a traditional teaching approach although they have a high level of content knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key requirements for becoming a certified teacher in the twenty-first century is mastery of technological pedagogical content (Ufuk, 2021). In today's professional teacher development activities, our educational system faces a great need to improve teachers' capacities to integrate technology-mediated learning into their instruction.…”
Section: Teachers' Professional Approachmentioning
confidence: 99%
“…E-learning is one of the most successful means to provide this rich educational environment. Education policies seek to promote teachers to implement online teaching activities and help their students to get engaged in learning and teaching activities (Carrillo and Flores, 2020;Uluçınar, 2021). Teachers play a significant role in integrating technology in teaching and learning (Güngör et al, 2022;Huber and Helm, 2020).Students have the responsibility to search for information and formulate it, which develops their thinking skills and e-learning.…”
Section: Introductionmentioning
confidence: 99%